Preparation and characterization of magnetic hollow Fe3O4/P(GMA‐EGDMA)‐SO3H/Au‐PPy recyclable catalyst for catalytic reduction of 4‐nitrophenol. (3rd October 2018) - Ma, Mingliang; Yang, Yuying; Feng, Renjun; Jia, Li; Chen, Guopeng; Li, Wenting; Lyu, Ping
Abstract : A highly effective and stable hollow Fe3 O4 /P(GMA‐EGDMA)‐SO3 H/Au‐PPy catalyst was prepared. Monodisperse hollow Fe3 O4 microspheres were synthesized using a hydrothermal method. As the catalyst support, magnetic hollow Fe3 O4 /P(GMA‐EGDMA) microspheres with core–shell structure were prepared by distillation precipitation polymerization. Then sulfonic acid groups (─SO3 H) were introduced into the surface of the support by surface modification. Au 3+ could be adsorbed by coordination with ─SO3 H and underwent redox reactions with added pyrrole monomers. Finally, an Au–polypyrrole (PPy) layer was formed on the surface of the Fe3 O4 /P(GMA‐EGDMA)‐SO3 H microspheres. The synthesized material was characterized using various techniques. Results indicated that the as‐prepared hollow Fe3 O4 /P(GMA‐EGDMA)‐SO3 H/Au‐PPy catalyst had excellent catalytic activity and exhibited reusability for the reduction reaction of 4‐nitrophenol. In addition, the catalyst was reusable for at least ten successive cycles. Abstract : A highly effective and stable hollow Fe3 O4 /P(GMA‐EGDMA)‐SO3 H/Au‐PPy catalyst was prepared and characterized. The catalyst had excellent activity and exhibited reusability for the reduction reaction of 4‐nitrophenol. In addition, the catalyst was reusable for at least 10 successive cycles.